Gender gaps in financial literacy in three Southern Cone countries: Argentina, Chile, and Paraguay - José Espinoza-Delgado; Jacques Silber (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2022)
Understanding why women are less financially literate than men is crucial for developing effective policies that decrease gender inequalities and improve women's financial literacy, agency and empowerment. Accordingly, in this paper, we adopt a multidimensional approach to measure financial literacy; rather than focusing solely on financial knowledge, as most empirical work has done, we also take into account what has been referred to in the literature as financial behavior and financial attitude. We analyze financial capability data from Argentina, Chile and Paraguay and consider the answers given to 27 questions covering the three domains mentioned above. We find that there are statistically significant gender differences in these countries, which we confirm through extensive econometric analysis. We also conduct a traditional Oaxaca-Blinder decomposition, which indicates that the respective role played by the "explained" and "unexplained" part varies across countries.
Keywords: D14; G11; G41; I24; 330; Gender inequality; financial literacy; South America; Argentina; Chile; Paraguay